Noncoding RNAs: an emerging modulator of drug resistance in pancreatic cancer - Wei, Ling; Sun, Jujie; Wang, Xingwu; Huang, Yizhou; Huang, Linying; Han, Linyu; Zheng, Yanxiu; Xu, Yuan; Zhang, Nasha; Yang, Ming (Frontiers in Cell and Developmental Biology, 2023)
Pancreatic cancer is the eighth leading cause of cancer-related deaths worldwide. Chemotherapy including gemcitabine, 5-fluorouracil, adriamycin and cisplatin, immunotherapy with immune checkpoint inhibitors and targeted therapy have been demonstrated to significantly improve prognosis of pancreatic cancer patients with advanced diseases. However, most patients developed drug resistance to these therapeutic agents, which leading to shortened patient survival. The detailed molecular mechanisms contributing to pancreatic cancer drug resistance remain largely unclear. The growing evidences have shown that noncoding RNAs (ncRNAs), including microRNAs (miRNAs), long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs), are involved in pancreatic cancer pathogenesis and development of drug resistance. In the present review, we systematically summarized the new insight on of various miRNAs, lncRNAs and circRNAs on drug resistance of pancreatic cancer. These results demonstrated that targeting the tumor-specific ncRNA may provide novel options for pancreatic cancer treatments.